2019
DOI: 10.1002/srin.201800582
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of the Goss Orientation in Non‐Oriented Electrical Steel and the Evolution of the Goss Texture during Thermomechanical Processing

Abstract: During the manufacturing of non-oriented electrical steel laminations for electric motor or generator applications, the Goss ({110}<001>) texture frequently appears in several stages of the processing. To understand the origin and the evolution of this texture, a non-oriented electrical steel (2.8 wt% Si) is processed through hot rolling, hot band annealing, cold rolling and final annealing, and the origins of the Goss orientation and the evolution of the Goss texture in these processes are investigated by ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Goss subgrains appeared preferentially within striated structures, such as shear bands, in Figure 5a, which resulted in the formation of Goss recrystallization textures at shear bands during annealing. The misorientation between Goss and {111}<112> recrystallized grains was <110>30 • , indicating that the grain boundaries between Goss and {111}<112> recrystallized grains had the highest migration rate [23]. Goss recrystallization could increase by swallowing the surrounding {111} deformed matrix at the initial stage of recrystallization.…”
Section: Nucleation and Recrystallization At Grain Boundariesmentioning
confidence: 99%
“…Goss subgrains appeared preferentially within striated structures, such as shear bands, in Figure 5a, which resulted in the formation of Goss recrystallization textures at shear bands during annealing. The misorientation between Goss and {111}<112> recrystallized grains was <110>30 • , indicating that the grain boundaries between Goss and {111}<112> recrystallized grains had the highest migration rate [23]. Goss recrystallization could increase by swallowing the surrounding {111} deformed matrix at the initial stage of recrystallization.…”
Section: Nucleation and Recrystallization At Grain Boundariesmentioning
confidence: 99%
“…At the same time, it is also accompanied by the change of microstructure and texture different from that of conventional thickness. The essential difference between a hot-rolled sheet and a cold-rolled sheet is that there is a significant texture and microstructure gradient along the thickness direction of the hot-rolled sheet (or named texture and microstructure inhomogeneity), [1][2][3][4][5] which is manifested by the presence of the strong shear texture in the surface caused by the friction between rolls and sheet surface at high temperature and typical deformed α-fiber grains in the central layer. The shear microstructure shows that the fine equiaxed grains are dominated by dynamic recrystallization, or mixed structures of equiaxed grains and deformed grains, while the shear textures contain Goss texture {110}<001>, Brass texture {110}<112>, and Copper texture {112}<111> with different intensities.…”
Section: Introductionmentioning
confidence: 99%
“…The microstructure and texture gradient along the thickness direction of the hot-rolled sheet is affected by not only Si contents and other alloy elements, [4,5,7,9,10] but also by hot-rolled heating temperature, hot rolling finishing temperature, and coiling temperature. [11][12][13][14][15] The thickness of the fine-grained zone with shear orientation on the surface of the hot-rolled sheet varies, [1][2][3][4][5] which affects the competition between the surface layer and the central layer with different recrystallization behaviors during normalization and the normalization temperature or time required to achieve uniform grain size. In short, depending on the extent of microstructure and texture gradients in a hot-rolled sheet, the normalization temperature or holding time to achieve a uniform and coarse-grained microstructure before cold rolling will be different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous investigations showed that deformation conditions such as temperature and strain have great influences on typical textures in non-oriented electrical steel. [12][13][14][15][16][17][18][19][20] The typical textures concerned are desired textures such as Cube ({001} h100i) texture, Goss ({011} h100i) texture, rotated cube ({001} h110i) texture, and h-fiber (h100i//ND) as they have h100i axes which are the direction of easy magnetization and undesired c-fiber (h111i//ND, normal direction). [21][22][23][24] A great deal of experimental effort has been made to produce cube-textured electrical steels.…”
Section: Introductionmentioning
confidence: 99%